The astonishing work of Tezuka Osamu [1962-1988] - Tezuka, Osamu (New York : Kimstim, 2009)
Aru machikado no monogatari = Tales of the street corner ## Osu = Male ## Memorii = Memory ## Ningyo = Mermaid ## Shizuku = The drop ## Pictures at an exhibition ## Sōseiki = The genesis ## Jumping ## Broken down film ## Osu = Push ## Muramasa = Muramasa ## Legend of the forest ##
Dialog in Japanese with optional subtitles in English.
film
Keywords: Osamu, Tezuka